SECURING MICROFLORA ROLE IN CLEARING THE GROUND WATER COMPLEX PHYSICAL CHEMISTRY - , А. Н. (Municipal economy of cities. Series: «Economy science», 2013)
The issues of intensification of treatment of groundwater complex physical and chemical composition.